Second dose of measles-containing vaccine coverage and associated factors among children aged 24–36 months in Gondar city, Central Gondar, Northwest Ethiopia, 2023 - Adisu, Molalign Aligaz; Bogale, Worknesh Akanaw; Alemu, Tewodros Getaneh (Frontiers in Public Health, 2024)
Background Measles caused 207,000 deaths worldwide in 2019. Ethiopia ranks among the top 10 countries in the world with the highest number of measles cases. However, the coverage of the second dose of measles-containing vaccine (MCV2) remains low. To increase coverage, the government of Ethiopia launched a nationwide measles vaccination campaign. Despite this intervention, the coverage is still below target, and there is scarce information in the study area. Therefore, this study aimed to assess MCV2 coverage and associated factors among children aged 24–36 months in Gondar city, Central Gondar, Northwest Ethiopia, 2023. Methods A community-based cross-sectional study was conducted among 621 children aged 24–36 months using a systematic random sampling technique from 25 April to 25 May. A pre-tested, interviewer-administered, and structured questionnaire was used and collected using Kobo Toolbox and then transferred to Stata version 17 for further analysis. The binary logistic regression model was used to identify factors, and the presence of an association was declared using a p-value of <0.05. Similarly, an adjusted odds ratio with a 95% confidence interval was used to interpret the direction and strength of an association. Results A total of 621 children, with a response rate of 98.1%, participated in the study. The coverage of the second dose of MCV was 75.68% (95% CI: 72.1–78.9). The following factors were significantly associated with measles-containing vaccine second dose (MCV2) coverage: father as the household head (AOR: 3.06, 95% CI: 1.43–6.44), first birth order (AOR: 4.45, 95% CI: 1.21–16.3), four and above antenatal care (ANC) follow-ups (AOR: 5.18, 95% CI:1.62–16.5), postnatal care (PNC) service utilization (AOR: 2.57, 95% CI:1.27–5.15), at least two doses of vitamin A uptake (AOR: 6.39, 95% CI: 2.67–15.2), mothers having high awareness (AOR: 1.97, 95% CI:1.15–3.4), and good perception (AOR: 3.6, 95% CI: 2–6.47) about measles vaccination. Conclusion and recommendations The coverage of MCV2 in the study area is lower than the national and global target of above 95%. Head of household, birth order, ANC follow-up, PNC service utilization, vitamin A uptake, awareness, and perception of mothers about measles vaccination were significant factors for MCV2 coverage. Creating awareness, increasing the perception of mothers about measles vaccination, and strengthening the ANC and PNC services will increase the coverage.